Effect of Imiquimod on Tachyzoites of Toxoplasma gondii and Infected Macrophages in vitro and in BALB/c Mice - Zaki, Leila; Ghaffarifar, Fatemeh; Sharifi, Zohreh; Horton, John; Sadraei, Javid (Frontiers in Cellular and Infection Microbiology, 2020)
The commonly prescribed drugs for toxoplasmosis have not yet been completely successful because of their unwanted side effects. Imiquimod has ability to moderate immune response and used to treat a wide variety of infections and tumors. The aim of the present study was to evaluate the effect of imiquimod on the tachyzoites of Toxoplasma gondii and infected macrophages in vitro and in vivo. The viability of T. gondii was assessed in the presence of various concentrations of imiquimod by direct counting after 3 and 24 hours. The MTT assay was used to identify the viability of uninfected macrophages. The apoptotic effects of this drug was determined with flow cytometry assay on the tachyzoites and infected macrophages, respectively. For evaluation of parasite load in pre-treatment or post-treatment of macrophages quantitative polymerase chain reaction (qPCR) was performed. In order to in vivo experiments, BALB/c mice received imiquimod before and after challenge with parasites. Furthermore, the mortality rate of mice, parasite numbers in spleen, and the INF-γ and IL-4 cytokines levels were evaluated. Imiquimod demonstrated anti-Toxoplasma effects by reducing the number of tachyzoites. The results of flow cytometry for drug-treated tachyzoites showed that apoptosis production did not rise significantly relative to the control group (p<0.05). Moreover, apoptosis rate was enhanced in infected macrophages with a reducing concentration of imiquimod. The parasitic burden in pretreatment of macrophages with imiquimod before infection was significantly lower than posttreatment of macrophages after infection (p<0.01). A remarkable reduction was observed in survival rate, parasite load and the INF-γ level in BALB/c mice that received imiquimod before parasitic challenge relative to those received drug after parasitic challenge(p<0.01). Imiquimod in the pretreated group had greater anti-Toxoplasma effects than imiquimod in posttreated group in vitro and in vivo. However, anti-Toxoplasma activity of imiquimod both therapeutically and prophylactically can be considered as a candidate drug against Toxoplasmosis.